1970
DOI: 10.3171/jns.1970.33.6.0718
|View full text |Cite
|
Sign up to set email alerts
|

External carotid-transverse sinus fistula

Abstract: ✓ A case of congenital fistula between the posterior auricular artery and the transverse sinus is described. A comment is added on the possible embryological mechanism producing these lesions, and the usual symptomatology and treatment are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

1974
1974
2013
2013

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…In the literature, reviews are few 17,3.11,22, and cases reports mainly describe individual therapeutic attempts in paediatric cases 6,7,8,10,12,21,23,24,26,27 or as part of an adult series 19,25 . In both populations much discussion has focussed on the congenital vs acquired character of the disease.…”
Section: Introductionmentioning
confidence: 98%
“…In the literature, reviews are few 17,3.11,22, and cases reports mainly describe individual therapeutic attempts in paediatric cases 6,7,8,10,12,21,23,24,26,27 or as part of an adult series 19,25 . In both populations much discussion has focussed on the congenital vs acquired character of the disease.…”
Section: Introductionmentioning
confidence: 98%
“…8.3) and developmental aneurysms (Fig. Other authors have also reported an association between DAVMs and vascular abnormalities such as aneurysms and vascular malformations involving brain, skin and bone (Debrun 1972, Heishima 1977, Djindjian 1978, Robinson 1970 (Table 8.3). Among the 23 patients, 9 had a history of trauma, but the trauma involved the head in only four.…”
Section: Pathophysiologymentioning
confidence: 87%
“…The DAVF in our patient presented as an IDAVF and involved the dorsal epidural venous system 2 . Although only 25 IDAVF cases have been reported in the literature, no IDAVF at the anterior condylar confluence have been described to date 2-32 .…”
Section: Discussionmentioning
confidence: 99%